The effectiveness of breathing exercises in reducing dyspnea in patients with heart failure: A systematic review - Kristian Ade Chandra; Tuti Herawati; Anggri Noorana Zahra (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Heart failure is a global health problem with a relatively high prevalence. Dyspnea is one of the typical symptoms of heart failure. Dyspnea can affect various aspects of life of people who are suffering from heart failure. Management of dyspnea is needed to reduce this problem and improve the quality of life of patients. One of the interventions that can be done is breathing exercises. Purpose: To reduce dyspnea in patients with heart failure. Method: A systematic review of articles obtained from several databases including Science Direct, Oxford, EBSCO, PUBMED, and Sage Journals, from 2015 to 2024. Results: Based on the results of article screening based on the criteria in this study, 7 articles were obtained that explained the effectiveness of breathing exercises to reduce dyspnea in heart failure. Conclusion: Breathing exercises can be considered as a non-pharmacological therapy to reduce dyspnea in heart failure.